Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors in Treatment of Metastatic Non-Small Cell Lung Cancer, with a Focus on Afatinib - Morin-Ben Abdallah, Sami; Hirsh, Vera (Frontiers in Oncology, 2017)
Somatic epidermal growth factor receptor (EGFR) mutations are present in around 50% of Asian patients and in 10–15% of Caucasian patients with metastatic non-small cell lung cancer (NSCLC) of adenocarcinoma histology. The first-generation EGFR-tyrosine kinase inhibitors (TKIs) gefitinib and erlotinib have demonstrated improved progression-free survival (PFS) and response rates but not overall survival (OS) benefit in randomized phase III trials when compared with platinum-doublet chemotherapy. All patients treated with EGFR-TKIs will eventually develop acquired resistance to these agents. Afatinib, an irreversible ErbB family blocker, has shown in two randomly controlled trials in patients with EGFR-activating mutations, a significant improvement in PFS and health-related quality of life when compared to platinum-based chemotherapy. Afatinib improved OS in patients with Del19 mutations. In patients having progressed on first-generation EGFR-TKIs, afatinib did lead to a clinical benefit. A randomly controlled trial showed that PFS was significantly superior with afatinib vs. erlotinib in patients with squamous NSCLC in the second-line setting. A phase IIb trial comparing afatinib and gefitinib in first-line EGFR positive NSCLC showed significantly improved PFS with afatinib but OS was not significantly improved.